Functional and Metabolic Characterization of Microglia Culture in a Defined Medium - Montilla, Alejandro; Zabala, Alazne; Matute, Carlos; Domercq, María (Frontiers in Cellular Neuroscience, 2020)
Microglia are the endogenous immune cells of the brain and act as sensor of infection and pathologic injury to the brain, leading to a rapid plastic process of activation that culminates in the endocytosis and phagocytosis of damaged tissue. Microglia cells are the most plastic cells in the brain. Microglia isolation from their environment as well as culturing them in the presence of serum alter their function and lead to a rapid loss of their signature gene expression. Previous studies have identified pivotal factors allowing microglia culture in the absence of serum. Here, we have further characterized the function, expression of markers, metabolic status and response to pro and anti-inflammatory stimulus of microglia isolated by magnetic-activated cell sorting and cultured in a chemically defined medium. We have compared this new method with previous traditional protocols of culturing microglia that use high concentrations of serum.